(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Problem-oriented learning (PBL) is necessary for constructive, independent, collaborative and contextual learning of students. This article presents a comparative analysis of the training cycle using PBL for students of the 1st semester at the initial stage of training in physiology and for students of the 2nd semester who have already completed the basic course of physiology. We observed the dynamics in the groups and the process of assimilation of the material. The results of the study showed that the students of the 2nd semester have a positive correlation between group dynamics, self-study and learning outcomes is more pronounced than that of beginning students. Our results give grounds for the restructuring of the educational cycle, which is especially important for beginning students in mastering PBL.